Antecedents of Turnover Intention in Millennial Employees: Employee Engagement and Organizational Culture as Mediation Variables - Kaffaso, Yoseph Vernon Suardi; Mahyuni, Luh Putu (GoAcademica Research & Publishing, 2024)
This research aims to find the antecedents of turnover intention in millennial employees, where employee engagement and organizational culture mediate. This research was conducted at banks in Bali Province. The population was all banking employees in Bali Province. From this population, 230 samples were taken, namely bank employees. Data was collected using a questionnaire method. The collected data was then analyzed using Structural Equation Modeling (SEM) Partial Least Squares (PLS). This research shows that professional identity and work environment negatively impact turnover intention, and professional identity positively impacts employee engagement and organizational culture. Next, the work environment positively impacts employee engagement and organizational culture. Employee engagement has a negative and significant effect on turnover intention; Organizational culture does not affect turnover intention, and Employee engagement can mediate the influence of professional identity on turnover intention. Employee engagement can mediate the influence of the work environment on turnover intention. Organizational culture cannot mediate the influence of professional identity on turnover intention. And organizational culture cannot mediate the influence of the work environment on turnover intention.”